The last samurai [videorecording (DVD)] - Cruise, Tom, 1962-; Zwick, Edward; Logan, John, 1961-; Watanabe, Ken, 1959-; Wagner, Paula, 1946- (Warner Home Video, 2003)
"Tom Cruise plays Civil War hero Capt. Nathan Algren, who comes to Japan to fight the Samurai and ends up pledging himself to their cause. Ken Watanabe ... plays Katsumoto, a Samurai leader facing a vanishing way of life, whose destiny becomes intertwined with that of the American captain. Edward Zwick ... directs this sweeping and emotional epic tale of the birth of modern Japan."--Back cover.